Butt or face? : ador-a-butts! - Lavelle, Kari (Butt or face?, 2026)
Butt or Face? Volume 4: Adora-Butts is an illustrated guessing-game book that invites readers to identify animals from close-up photographs. Each page presents a detailed image of part of an animal, challenging readers to determine whether the image shows the animal's face or its rear. The following page reveals the full photograph and the correct answer. The book features a variety of animals from around the world, including the pygmy seahorse, pink fairy armadillo, and quokka, and provides brief facts about each species along with information about camouflage and other animal adaptations.